WETTING OF CORK BY POLYMERIC ADHESIVES - ADAO, M H; CABRITA, G M; GOMES, C M; ALMEIDA, B S; FERNANDEZ, A C; Bordado, J C (JOURNAL OF ADHESION SCIENCE AND TECHNOLOGY, 1993)
The cohesion of cork agglomerates is determined by the strength of the adhesive joint established between the polymeric adhesive and the cork particles. The ability of adhesives to form good joints depends, among other factors, on the wetting of cork by the adhesives. The main objective of this research was to study the behaviour of adhesive drops deposited on cork substrates through measurements of contact angles and their time dependence. Several polyurethane prepolymers were tested to establish a correlation between the wetting characteristics and the chemical structure and physical properties of the adhesives. The effect of the morphology of cork on the interfacial properties was also investigated. The initial contact angles were related to the chemical nature of the adhesive. The kinetics of the wetting process were found to depend mainly on the viscosity of the adhesive.
Keywords: CONTACT ANGLE; CORK AGGLOMERATES; POLYMERIC ADHESIVES; WETTING